2019
DOI: 10.20471/acc.2019.58.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Stress Ulcer Prophylaxis as a Risk Factor for Tracheal Colonization and Hospital-Acquired Pneumonia in Intensive Care Patients: Impact on Latency Time for Pneumonia

Abstract: SUMMARY Stress ulcer prophylaxis is associated with bacterial colonization of respiratory tract. The aims of our study were to determine risk factors for trachea colonization (TC), colonization of pharynx (CP) or stomach (CD) and hospital-acquired pneumonia (HAP), and divide the factors into those with high risk and low risk. The study population (ventilated intensive care unit (ICU) patients eligible to receive stress ulcer prophylaxis) was randomized to receive one of three different treatment pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…It was still controversial whether SUP increases the risk of hospital-acquired pneumonia and CDI because SUP use might decrease gastric acidity, altering normal intestinal flora and the overgrowth of gastric bacteria. 21 The results of the present study did not correspond with previous studies, 11,22,23 which indicated that SUP use was associated with an increased risk of infectious complications. In our study, SUP use may have no impact on ICU or hospital LOS in this study population.…”
Section: Discussioncontrasting
confidence: 99%
“…It was still controversial whether SUP increases the risk of hospital-acquired pneumonia and CDI because SUP use might decrease gastric acidity, altering normal intestinal flora and the overgrowth of gastric bacteria. 21 The results of the present study did not correspond with previous studies, 11,22,23 which indicated that SUP use was associated with an increased risk of infectious complications. In our study, SUP use may have no impact on ICU or hospital LOS in this study population.…”
Section: Discussioncontrasting
confidence: 99%
“…The control group was placebo in 40 trials and no prophylaxis in 25 trials. Of note, five trials did not report on any of our outcomes and were thus not included in any quantitative analyses . Characteristics of the included trials are presented in Table and full schematic overview of results in Table , in the ESM.…”
Section: Resultsmentioning
confidence: 99%
“…Three trials were adjudicated as having overall low risk of bias; the remaining trials were adjudicated as having an overall high risk of bias (Figure 2). Only six and eight trials were adjudicated as low risk of bias in the domains for ‘selective reporting’ and ‘allocation concealment’ respectively. More than 75% of the trials were at unclear or high risk of financial bias (‘other bias’ domain), mostly because there were no declarations about funding at all.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in a study from China, in COVID-19 patients with PaO 2 /FIO 2 <300 mm Hg combining prone position with HFNC significantly improved ventilation-perfusion mismatch and proved to be a good strategy in avoiding intubation and reducing the medical staff workload 9 . It must also be noted that, although recently published data suggest that stress ulcer prophylaxis might increase the risk of bacterial superinfection 10 , in this patient it was not the case and the collected sputum specimens showed no pathogen growth.…”
Section: Discussionmentioning
confidence: 56%